Andrew Jackson : 7th president of the United States - Stefoff, Rebecca, 1951- (Ada, Okla. : Garrett Educational Corp., 1988)
A biography of the seventh President describing his frontier childhood, education, career as a soldier and politician, and his new approach to the presidency.
Includes index.
Bibliography: p. 113-114.
1100
Accelerated Reader AR
Keywords: Jackson, Andrew, -- 1767-1845 -- Juvenile literature; Jackson, Andrew, -- 1767-1845.; Presidents -- United States -- Biography -- Juvenile literature; Presidents